2008
DOI: 10.1080/10408390701691059
|View full text |Cite
|
Sign up to set email alerts
|

Potato: A Comparative Study of the Effect of Cultivars and Cultivation Conditions and Genetic Modification on the Physico-Chemical Properties of Potato Tubers in Conjunction with Multivariate Analysis Towards Authenticity

Abstract: Potato (Solanum tuberosum L.) is a highly nutritious, mild flavored, easy to blend food that has many possibilities for "building in" desired nutrients. Varietal and environmental differences are known to exist in the shape, size, and nutritional content of potatoes. Different populations opt for varying sensory properties in relation to their diets. Potatoes are a low energy food in comparison to cereals and legumes. The aim of this review was to present an update of the currently conducted studies both on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 94 publications
1
22
0
Order By: Relevance
“…Multivariate statistical methods have been widely used in the authentication of foods to enable the visualisation of data when more than three variables have been measured (Arvanitoyannis et al, 1999;Tzouros & Arvanitoyannis, 2001;Arvanitoyannis & Van Houwelingen-Koukaliaroglou, 2003;Arvanitoyannis et al, 2005;Vlachos & Arvanitoyannis, 2008;Arvanitoyannis et al, 2008;Arvanitoyannis & Vlachos, 2009). The mathematical basis will be representation and manipulation of data by vectors and matrices (Kellner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate statistical methods have been widely used in the authentication of foods to enable the visualisation of data when more than three variables have been measured (Arvanitoyannis et al, 1999;Tzouros & Arvanitoyannis, 2001;Arvanitoyannis & Van Houwelingen-Koukaliaroglou, 2003;Arvanitoyannis et al, 2005;Vlachos & Arvanitoyannis, 2008;Arvanitoyannis et al, 2008;Arvanitoyannis & Vlachos, 2009). The mathematical basis will be representation and manipulation of data by vectors and matrices (Kellner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The contents of protein, starch, sugars and lipids were determined. An increase was recorded in TL overexpressing 14-3-3 protein from Cucurbita pepo 28 . Analysis of plants suggested that the function of the isolated 14-3-3 isoform is in the control of carbohydrate and lipid metabolism.…”
Section: Total Lipids and Lipid Classesmentioning
confidence: 98%
“…The environmental variation on transgenic potatoes, should be examined more in food safety aspects as crops could be grown under different conditions, with respect to variation of protein expressions in potato tubers whether transgenic individuals could have significant deviation on their expression beyond the variation of their non-transgenic comparators. 38,39) In vitro mast cell activation studies are useful to understand the biological significance of differences in expression of allergenic proteins in plants. Recently, we developed an in vitro cell activation system using a humanized FceRI-expressing rat mast cell line (RS-ATL8).…”
Section: Discussionmentioning
confidence: 99%